Kinetic and biocompatibility investigation on the catalytic ring opening polymerization of L-lactide in bulk using cyclic Bu2Sn initiators derived from ethylene glycol, pentaerythritol and cloisite 30B - Mohite, Kavita K.; Garnaik, Baijayantimala (Polyhedron, 2020)
In the present work, considering a green approach, PLLA was synthesized by the ring-opening polymerization of L-LA using various cyclic initiators (2,2-dibutyl-2-stanna-1,3-dioxacyclo ethane (1), spirocyclic tin (3) and cloisite modified tin (5)). PLLA was characterized by size exclusion chromatography, differential scanning calorimetry, H-1 and C-13 NMR, XRD and MALDI-TOF. The molecular weight distribution was narrow (<1.5) for both low and high molecular weights (>85,000 g/mol). An X-ray study showed the crystalline nature of PLLA, irrespective of the different types of initiators and polymerization conditions. A kinetic investigation showed that all polymerizations were first order with respect to the monomer and no termination reactions occurred during the polymerization. MALDI-TOF spectra of PLLA chains doped with Na+ and K+ cations show that the PLLA prepared using initiators 1 and 3 have hydroxyl and carboxyl end groups without incorporation of tin. The MALDI-TOF spectrum of PLLA prepared using initiator 5 also enabled the simultaneous detection of the linear and cyclic structure of PLLA without tin. Biocompatible and biodegradable PLLA was obtained, which could be used for biomedical applications. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Cloisite modified tin; Cyclic tin initiator; MALDI-TOF; Poly (L-Lactide); Spirocyclic